“It’s not easy but it's still possible to be an abstainer here”: Non-Drug Use Among Young Men in a Slum Area in Makassar, Indonesia - Nasir, Sudirman; Rosenthal, Doreen; Moore, Timothy (International Journal of Criminology and Sociology, 2014)
This qualitative study explores the social context and protective factors that enable young men in a slum area (lorong) in Makassar, Indonesia, to abstain from using drugs. Semi-structured interviews, conducted with fifteen male non-drug users in the lorong showed, despite living in a drug risk environment, non-drug users were involved in neither the drug scene nor street culture. There were two main reasons for this: their employment opportunities, albeit in low paid jobs and the informal economy, and their schooling. These non-users asserted that respectability and the status of rewa (a local construct of masculinity) should and could be achieved through traditional means, i.e. employment providing legitimate income and education leading to a career. Their work provides both direct benefit, i.e. legitimate income (economic capital), and indirect benefits such as meaningful activities and structured time. Employment and schooling also generated a respectable identity (symbolic and cultural capital), wider social networks (bridging social capital) and the opportunity for upward mobility. All of these enable them to have a stake within mainstream society and are incentives for them to abstain from drug taking. This study demonstrates the crucial role of direct and indirect benefits of employment and of economic, symbolic, cultural and social capital in understanding the social context of non-drug use among young men in the lorong. The findings suggest protagonists of drug policy reform and implementation in Indonesia should be more cognizant of social marginalization in the lorong, and of the need to improve young people’s access to employment and education, in order to decrease the likelihood of drug initiation and use.